Determinants of nurse absenteeism and intent to leave: An international study. (13th September 2018) - Burmeister, Elizabeth A.; Kalisch, Beatrice J.; Xie, Boqin; Doumit, Myrna A. A.; Lee, Eunjoo; Ferraresion, Annamaria; Terzioglu, Fusun; Bragadóttir, Helga
Abstract: Aim: To determine factors associated with nurses' intent to leave their positions and absenteeism. Background: There is a recognized global shortage of nurses but limited data describing and determining factors associated with nurse absenteeism and intent to leave. Methods: This study involved a secondary analysis of the results from direct‐care registered nurses' responses to the MISSCARE Survey, with data from seven countries included. Multi‐level modelling was used to determine nurse characteristics and working environment factors associated with nurse absenteeism and intent to leave. Results: The level of absenteeism and intent to leave varied significantly across countries, with registered nurses in Lebanon reporting the highest intention to leave within 12 months (43%) and registered nurses in Iceland and Australia the highest level of absenteeism (74% and 73%, respectively). Factors associated with outcomes included perceived staffing adequacy of unit, job satisfaction, and age of the nurse. Conclusions: A significant difference between countries was identified in nurse absenteeism and intent to leave. Increased perception of unit staffing inadequacy, lower job satisfaction, less nurse experience, and younger age were significant contributors to nurse absenteeism and intent to leave. Implications for Nursing Management: These findings suggest that regardless of country and hospital, by ensuring that units are adequately staffed and increasing job satisfaction, younger, less experienced nurses can be retained and absenteeism reduced.